Maternal near miss in Ethiopia: Protective role of antenatal care and disparity in socioeconomic inequities: A systematic review and meta-analysis - Belayneh Mengist; Melaku Desta; Abera Kenney Tura; Tesfa Dejenie Habtewold; Amanuel Abajobir (Elsevier, 2021)
Background: The burden of maternal near miss (MNM) is an important public health problem in low and middle income countries including Ethiopia despite ongoing initiatives both at regional and national levels. Intricate and persistent socioeconomic inequities as well as poor health care seeking behavior contribute to MNM, although extant evidence is inconsistent and inconclusive. This systematic review and meta-analysis was therefore aimed to estimate the pooled national burden of MNM and contributing factors in Ethiopia. Methods: This systematic review and meta-analysis pursued the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline, and was registered on PROSPERO (CRD42018105518). An extensive search of databases including Pub Med, Web of Science, CINHA and African Journals Online was conducted to retrieve potential published articles. The Newcastle-Ottawa quality assessment tool was used to assess the quality of eligible studies. Inverse variance test was used to assess heterogeneity and publication bias was checked by the funnel plot and Egger's test. STATA version 14 was used to carry out the meta-analysis, and estimate the magnitude and associated factors of MNM using a random-effects model. Results: Eleven studies, with a total of 98,268 women, were included in the meta-analysis. The pooled burden of MNM was 12.57% (95%CI: 10.26, 14.88). The highest and lowest burden was observed in Amhara region (26.75% (95%CI: 22.46-31.05) and Addis Ababa; (0.8% (95%CI: 0.7, 0.9), respectively. Mothers who had antenatal care visit were 67% less likely to experience MNM [OR = 0.33, 95%CI: 0.22, 0.49]. Notwithstanding, women who were rural residents [OR = 2.7, 95%CI: 1.39, 5.25], did not have formal education [OR = 2.48, 95% CI: 1.58, 3.89] and were unmarried [OR = 1.69, 95%CI: 1.03, 2.78] had higher odds of MNM. Conclusions: One out of eight women experience MNM in Ethiopia. Antenatal care visit is a protective factor to MNM, although disadvantaged socioeconomic conditions contribute to two fold of the near misses. Improving the maternal health care services utilization and women empowerment would reduce the burden of MNM.